2023
DOI: 10.1111/jre.13094
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant irisin enhances the extracellular matrix formation, remodeling potential, and differentiation of human periodontal ligament cells cultured in 3D

Abstract: Background Irisin is expressed in human periodontal ligament (hPDL), and its administration enhances growth, migration and matrix deposition in hPDL cells cultured in monolayers in vitro. Objectives To identify whether irisin affects the gene expression patterns directing the morphology, mechanical properties, extracellular matrix (ECM) formation, osteogenic activity and angiogenic potential in hPDL cell spheroids cultured in 3D. Materials and Methods Spheroids of primary human hPDL cells were generated in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…Existing evidence suggests that recreational physical activity may have a protective effect on periodontal health [60,61]. Indeed, current in vitro studies reveal the involvement of irisin in differentiation, growth, and migration, as well as extracellular matrix formation in various dental cell lines [62][63][64][65][66][67][68][69][70][71][72]. It has been reported that the p38 MAPK and AKT signaling pathways are involved in irisin's effects [62,65,72].…”
Section: Irisin and Oral Healthmentioning
confidence: 99%
“…Existing evidence suggests that recreational physical activity may have a protective effect on periodontal health [60,61]. Indeed, current in vitro studies reveal the involvement of irisin in differentiation, growth, and migration, as well as extracellular matrix formation in various dental cell lines [62][63][64][65][66][67][68][69][70][71][72]. It has been reported that the p38 MAPK and AKT signaling pathways are involved in irisin's effects [62,65,72].…”
Section: Irisin and Oral Healthmentioning
confidence: 99%
“…Recent studies reveal that irisin might play a protective role in joint health, preventing or slowing OA progression. In vitro studies underscore irisin’s role in increasing collagen type II and aggrecan ECM production by chondrocytes [ 150 ] as well as chondrogenic differentiation [ 151 ] with potential positive effects on cartilage maintenance and repair. Irisin was shown to decrease inflammatory cytokines in chondrocytes, including interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α), potentially protecting articular joints [ 152 ].…”
Section: Obesity and Mets Adipokine Disbalance Impact Oa Occurrence A...mentioning
confidence: 99%